Biocompatible Peritoneal Dialysis: The Target Is Still Way Off - Bartosova, Maria; Schmitt, Claus Peter (Frontiers in Physiology, 2019)
Peritoneal dialysis (PD) is a cost-effective, home-based therapy for patients with end-stage renal disease achieving similar outcome as compared to hemodialysis. Still, a minority of patients only receive PD. To a significant extend, this discrepancy is explained by major limitations regarding PD efficiency and sustainability. Due to highly unphysiological composition of PD fluids, the peritoneal membrane undergoes rapid morphological and long-term functional alterations, which limit the treatment and contribute to adverse patient outcome. This review is focused on the peritoneal membrane ultrastructure and its transformation in patients with kidney disease and chronic PD, underlying molecular mechanisms, and potential systemic sequelae. Current knowledge on the impact of conventional and second-generation PD fluids is described; novel strategies and innovative PD fluid types are discussed.